Respon Pemberian Pupuk MKP dan Jarak Tanam Terhadap Pertumbuhan dan Produksi Cabai Rawit (Capsicum frustescens L.). - Muhammad Imam Aminuddin (Agriculture faculty, Darul ‘Ulum Islamic University (UNISDA) of Lamongan, 2017)
Cayenne Pepper production in East Java province by 2012 amounted to 244,040 Tonnes declining in 2013 become 226,990 Tons, whereas in Lamongan production of cayenne pepper going rise in 2011 a total of 9661.90 Tons in the year 2012 be a total amounting to 15,447 tons. The purpose of this research is to know the response the granting of MKP fertilizer and planting distance towards the growth and production of the cayenne pepper. This research was performed using Random Design methods Group (RAK) factorial, which consisted of two factors. Factor I namely Fertilizer MKP (P) consists of 4 levels, among other things: P1 = 1.5 grams. liter-1; P2 = 3 grams. liter-1; P3 = 4.5 g. liter-1; P4 = 6 grams. liter-1. While the Factor II namely trunks (J), consisting of: JI = 60 × 40 cm; J2 = 60 x 50 cm; J3 = 60 x 60 cm. The conclusions of this research are there interaction treatment granting MKP fertilizer concentration and trunks on the variables number of strands of leaf age 35 hst; the number of branches age 21 and 28 hst hst; percentage of the flower becomes fruit age 56 and 63 hst hst; the number of fruit per sample on the treatment of granting fertilizer MKP4 .5 grams. liter-1 trunks and 60 x 50 cm. best treatment Combinations shown on the treatment of the grant MKP fertilizer 4.5 g. liter-1 trunks and 60 x 50 cm.